Cadmium Contamination in Soil and Water and Its Impact on Human Health in Southeast Asia: A Systematic Review - Yulia Khairina Ashar; Andhara Tisya; Diva Keysha Aura Silalahi; Naila Nafisah; Dita Sajidah Poerwansyah (Indonesian Journal of Global Health Research, 2026)
This Cadmium (Cd) is a highly toxic heavy metal that poses serious threats to environmental and human health, especially in Southeast Asia, where industrial, mining, and agricultural activities are rapidly increasing. Chronic exposure to cadmium can lead to kidney damage, bone disorders, reproductive issues, and cancer, especially in areas relying on local water and food sources. This study employed a systematic literature review method, analyzing relevant studies published from databases including PubMed, Scopus, Google Scholar, and ScienceDirect. Keywords used included "cadmium contamination", "soil pollution", "water pollution", and "Southeast Asia". Inclusion criteria focused on studies reporting cadmium levels in soil or water and their health impacts in Southeast Asia. Cadmium contamination was reported in multiple countries, particularly in Thailand, Indonesia, and Vietnam. The primary sources of pollution include mining, fertilizer use, and industrial discharge. In many cases, cadmium levels in soil and water exceeded safety limits set by WHO and national standards and Health impacts. Cadmium contamination in Southeast Asia is a critical environmental and public health issue. Consistent findings across studies highlight the need for better waste management, stricter regulations, and regular monitoring. Public awareness and targeted interventions are essential to mitigate exposure and protect vulnerable populations.